2019
DOI: 10.18510/hssr.2019.7380
|View full text |Cite
|
Sign up to set email alerts
|

Product Aspects of Marketing Effort and Purchase Intention

Abstract: Purpose of Study: This article aims to analyze the effect of product aspects of marketing effort consisting of brand image, product quality, and service quality on consumer purchase intention. The sample of research is 100 consumer of Honda motorcycle in Surakarta city. Methodology: The sampling technique uses convenience sampling. Data analysis tools use multiple linear regression. Results: The results showed that brand image, product quality, and service quality significantly influence consumer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Since the brand image represented beliefs, ideas, and impressions of the product. Research of Yu et al, (2018) was contrary to Wiyadi & Ayunintyas (2019), the results indicated that negative brand image affecting the decrease in purchase intention of customers. Hence, the entrepreneurs or business owners would attempt to build the worth or value of brand image through various advertisements or promotion.…”
Section: The Relationship Between Brand Image (Bi) and Purchase Intention (Pi)mentioning
confidence: 67%
See 3 more Smart Citations
“…Since the brand image represented beliefs, ideas, and impressions of the product. Research of Yu et al, (2018) was contrary to Wiyadi & Ayunintyas (2019), the results indicated that negative brand image affecting the decrease in purchase intention of customers. Hence, the entrepreneurs or business owners would attempt to build the worth or value of brand image through various advertisements or promotion.…”
Section: The Relationship Between Brand Image (Bi) and Purchase Intention (Pi)mentioning
confidence: 67%
“…Producing good quality products by the firm, the consumer believed with the product and also made a satisfaction (Davis et al, 2003). This corresponded to Konuk (2018); Wiyadi & Ayunintyas (2019). They found that product quality had a positive influence on purchase intention.…”
Section: The Relationship Between Brand Image (Bi) and Purchase Intention (Pi)mentioning
confidence: 83%
See 2 more Smart Citations
“…Similar conclusions were reached by Alharthey (2019) , who found that service quality positively influenced consumers’ intentions to purchase groceries. Perceived service quality is one of the critical elements of online purchasing trust ( Wiyadi and Ayuningtyas, 2019 ). Most online selling platforms foster client confidence and enduring connections by providing high-quality services ( Shafiee and Bazargan, 2018 ).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%